Pengaruh Kontrol Diri terhadap Prokrastinasi Akademik Peserta Didik Kelas VIII di SMP Negeri 38 Padang - Wita Afriyeni; Rici Kardo; Rila Rahma Mulyani (Journal on Education, 2023)
The background of this research is that there are students who still like to procrastinate on work, are often late in submitting assignments, and cannot control themselves and time well. The purpose of this study was to describe: 1) Self-control, 2) Academic procrastination, 3) The effect of self-control on academic procrastination of class VIII students at SMP Negeri 38 Padang. This type of research is a quantitative descriptive method with simple regression analysis. In this study, data collection was carried out by observation and interviews. The population of this study was all students of class VIII at SMP Negeri 38 Padang totaling 240 people. The sampling technique used purposive sampling technique as many as 59 people. The instruments used were questionnaires and data analysis using percentage techniques. The results of this study indicate: 1) Self-control is in the good category, 2) Academic procrastination is in the fairly high category, and 3) There is an effect of self-control on academic procrastination in class VIII students at SMP Negeri 38 Padang of 19.6%. Based on the results of this study, it is recommended that students be able to increase self-control and reduce academic procrastination behavior, so that they can have a good influence on learning.